DIGITALISATION OF MSMES AND ITS IMPLICATION ON TAX COMPLIANCE - Loso Judijanto; Mahardika Catur Putriwana Malik (INJOSEDU: International Journal of Social and Education, 2025)
Digitalisation of MSMEs is an important part of economic transformation by providing various benefits, such as increased operational efficiency, easier market access, and business growth opportunities. In the process, digitalisation also has implications for the level of tax compliance of business actors. The use of digital technology, such as automated transaction recording and financial platform integration, provides more transparency into MSME business activities, making monitoring by tax authorities easier. This article discusses how the digitalisation of MSMEs can drive tax compliance through better access to the tax system, while emphasising the importance of tax education for MSME players to optimally fulfil their tax obligations. The main conclusion shows that the adoption of digital technology by MSMEs not only drives business growth, but also becomes a key driver in realising higher tax compliance.